Dietary Supplementation With Bacillus subtilis Direct-Fed Microbials Alters Chicken Intestinal Metabolite Levels - Park, Inkyung; Zimmerman, Noah P.; Smith, Alexandra H.; Rehberger, Thomas G.; Lillehoj, Erik. P.; Lillehoj, Hyun S. (Frontiers in Veterinary Science, 2020)
Direct-fed microbials (DFMs) are dietary supplements containing live microorganisms which confer a performance and health benefit to the host, but the mechanisms are unclear. Here, a metabolomics approach was used to identify changes in intestinal metabolite levels in chickens fed an unsupplemented diet or a diet supplemented with B. subtilis strain 1781 or strain 747. Body weight gains of chickens fed the B. subtilis-supplemented diets were increased, compared with chickens fed the unsupplemented diet. Compared with unsupplemented controls, the levels of 83 metabolites were altered (p < 0.05) (25 increased, 58 decreased) in chickens given the B. subtilis 1781-supplemented diet, while 50 were altered (p < 0.05) (12 increased, 38 decreased) with the B. subtilis 747-supplemented diet. Twenty-two metabolites were altered (p < 0.05) (18 increased, 4 decreased) in the B. subtilis 1781 vs. B. subtilis 747 groups. Changes in the levels of these intestinal biochemicals provided a distinctive biochemical signature unique to each B. subtilis-supplemented group, and were characterized by alterations in the levels of dipeptides (alanylleucine, glutaminylleucine, phenylalanylalanine, valylglutamine), nucleosides (N1-methyladenosine, N6-methyladenosine, guanine, 2-deoxyguanosine), fatty acids (sebacate, valerylglycine, linoleoylcholine), and carbohydrates (fructose). These results provide the foundation for future studies to identify biochemicals that might be used to improve poultry growth performance in the absence of antibiotic growth promoters.